The social and linguistic integration experiences of Ukrainian refugees through community and urban education courses in Iceland - Artëm Ingmar Benediktsson; Vander Tavares (Social Sciences and Humanities Open)
This study explores Ukrainian refugees’ perspectives on and experiences with courses aimed at developing L2 skills and facilitating social integration in Iceland. The theoretical framework draws on tenets of experiential education which emphasise learning through direct experience, active engagement, and reflection. The data originates from group interviews with seven Ukrainian refugees and individual interviews with two teachers of the courses. The findings illustrate a positive interplay between experiential learning, L2 development, and social integration. The refugee students experienced the courses as meaningful, engaging, and creative forms of learning, which contributed significantly to their development of cultural, social, and linguistic knowledge.